Bulbar urethroplasty using the dorsal approach: current techniques - Barbagli,Guido (2003)
INTRODUCTION: The use of flaps or grafts is mandatory in patients with longer and complex strictures. In 1995-96 we described a new dorsal onlay graft urethroplasty. Over time, our original technique was better defined and changed. Now this procedure (also named Barbagli technique) has been greeted with a fair amount of enthusiasm in Europe and in the United States. SURGICAL TECHNIQUE: The patient is placed in normal lithotomy position, and a midline perineo-scrotal incision is made. The bulbar urethra is then free from the bulbo-cavernous muscles, and is dissected from the corpora cavernosa. The urethra is completely mobilized from the corpora cavernosa, it is rotated 180 degrees, and is incised along its dorsal surface. The graft (preputial skin or buccal mucosa) or the flap is fixed and quilted to the tunica albuginea of the corporal bodies. The right mucosal margin of the opened urethra is sutured to the right side of the patch-graft. The urethra is rotated back into its original position. The left urethral margin is sutured to the left side of the patch graft and to the corporal bodies, and the grafted area is entirely covered by the urethral plate. The bulbo-cavernous muscles are approximated over the grafted area. A 16F silicone Foley catheter is left in place. COMMENTS: Dorsal onlay graft urethroplasty is a versatile procedure that may be combined with various substitute materials like preputial skin, buccal mucosa grafts or pedicled flaps.